Natural Food Additives - Prieto, Miguel A.; Otero, Paz (IntechOpen, 2022)
Although additives are regularly used in the food industry to improve the organoleptic properties or extend the shelf life of food products, some additives are known to be potentially hazardous if consumed in excess. Increasingly, consumers are avoiding these types of products, highlighting an overall trend toward developing a green and sustainable economy and the emergence of natural additives with equal or greater benefits than synthetic ones. This book is an introduction to the use of natural food additives. It includes eleven chapters that discuss emerging compounds used as food additives and active packaging, molecular gastronomy, enzyme production in the food industry, and much more.